Seasonal variations and environmental influences on dry eye operations in Japan - Yoshiaki Kabata; Ryo Terauchi; Tadashi Nakano (Scientific Reports)
Abstract The surface of the eye is constantly exposed to the external environment and is affected by atmospheric conditions and air pollution, and dry eye is a typical ocular surface disease. The aim of this study is to determine whether there are seasonal differences in the number of dry eye operations in Japan and to investigate whether meteorological conditions and air pollutants are related to. The operations were examined using the National Database of Health Insurance Claims and Specific Health Checkups of Japan (NDB) database from fiscal years 2019 to 2021. Temperature, atmospheric pressure, relative humidity, volume humidity, wind speed, sulfur dioxide (SO₂), nitrogen oxides X (NOX), photochemical oxidants (OX), carbon monoxide (CO) and particulate matter 2.5 (PM2.5) were considered. The number of dry eye operations was significantly higher in winter than in summer. (p = 0.0023) No significant differences were found among the other seasons. Volume humidity and temperature were strongly negative correlated, NOX and atmospheric pressure were strongly positive correlated.